Financial Report Analysis as a Basis for Assessing Franchise Companies Listed on the Indonesia Stock Exchange: (Case Study of PT. Hero Supermarket Tbk and PT Midi Utama Indonesia Tbk for the 2021-2023 Period) - Ombih Ajitama; Isni Mardiani; Puji Wahono; Indra Pahala (Transpublika Publisher, 2024)
The escalating number of franchise outlets in the current business landscape has triggered fierce rivalry among business owners. An effective way to reach a company's objectives is by evaluating its financial performance. To assess a company's performance, one can compare its ratios with those of similar companies. This research focused on public franchise companies like PT Hero Supermarket Tbk and PT Midi Utama Indonesia Tbk to determine which firm excels in terms of financial performance. Qualitative data, comprising company profiles and financial reports from 2021-2023, was utilized in this study. Secondary data, such as financial reports from 2021-2023 acquired from the Indonesia Stock Exchange (www.idx.co.id), were analyzed. A quantitative analysis was conducted on the balance sheet and income statement of the two companies. Liquidity ratios (Quick Ratio, Current Ratio), solvency ratios (DAR, DER), and profitability ratios (Net Profit Margin, ROA, ROE) were utilized in the analysis. Results indicated that the liquidity ratios of both companies fluctuated due to an increase in liabilities, surpassing current assets. Solvency ratios exhibited fluctuations caused by rising total debt, assets, and equity. Profitability ratios witnessed a decline in net profit due to higher costs of goods sold incurred by the company.